A Survey on Cross‐Virtuality Analytics. (8th February 2022) - Fröhler, B.; Anthes, C.; Pointecker, F.; Friedl, J.; Schwajda, D.; Riegler, A.; Tripathi, S.; Holzmann, C.; Brunner, M.; Jodlbauer, H.; Jetter, H.‐C.; Heinzl, C.
Abstract: Cross‐virtuality analytics (XVA) is a novel field of research within immersive analytics and visual analytics. A broad range of heterogeneous devices across the reality–virtuality continuum, along with respective visual metaphors and analysis techniques, are currently becoming available. The goal of XVA is to enable visual analytics that use transitional and collaborative interfaces to seamlessly integrate different devices and support multiple users. In this work, we take a closer look at XVA and analyse the existing body of work for an overview of its current state. We classify the related literature regarding ways of establishing cross‐virtuality by interconnecting different stages in the reality–virtuality continuum, as well as techniques for transitioning and collaborating between the different stages. We provide insights into visualization and interaction techniques employed in current XVA systems. We report on ways of evaluating such systems, and analyse the domains where such systems are becoming available. Finally, we discuss open challenges in XVA, giving directions for future research. Abstract : In Cross‐virtuality analytics, a novel field of research within immersive analytics and visual analytics, transitional and collaborative interfaces are used to seamlessly integrate different devices and support multiple users. The image shows example systems in this area from ongoing work by the authors.